Incidence of Non-Melanoma Skin Cancers in Salento (Southern Italy): A 15-Year Retrospective Analysis from the Cancer Registry of Lecce - Emiliano Sordi; Prisco Piscitelli; Carla Albanese; Anna Melcarne; Anna Tardio; Fabrizio Quarta; Enrico Greco; Alessandro Miani; Andrea Falco; Elisabetta De Matteis; Maurizio Congedo; Adele Civino (MDPI AG, 2023)
Background and Objectives: Non-melanoma skin cancers (NMSCs) include basal cell carcinoma (BCC) and squamous-cell carcinoma (SCC), as well as a wide range of rare skin tumors. NMSCs is the most frequently diagnosed type of tumor among Caucasians. We aimed at estimating the incidence and mortality of NMSCs in the Salento area (Lecce province, Southern Italy), whose population is assumed to experience heavy and frequent sun exposure due to climatic/environmental factors, both for working and leisure activities. Materials and Methods: We computed the incidence of NMSCs in the Province of Lecce by examining the comprehensive real-world data collected by the local cancer registry, which covers all the 830,000 inhabitants, over a period of fifteen years (from 2003 to 2017), with a focus on the latest 5 years (2013-2017) for the analysis of the different histologic morphologies of these tumors. The incidence of NMSCs has been described in terms of absolute frequencies, crude rates and age-adjusted direct standardized rates (DSR). Joinpoint analysis was used to examine temporal trends in the incidence of NMSCs and estimate annual percent changes (APCs). Results: During the period of 2003-2017, the incidence of NMSCs reached a direct standardized rate (DSR) of 162.62 per 100,000 in men (mortality 1.57 per 100,000) and 89.36 per 100,000 in women (mortality 0.52 per 100,000), respectively. The incidence significantly increased among both men and women across the entire period. Basal cell carcinoma (BCC), with its different morphologies, represented about 67.6% of the NMSCs in men (n = 2139 out of a total of 3161 tumors observed between 2013 and 2017) and about 75.8% of the NMSCs in women (n = 1718 out of a total of 2264 tumors from 2013 to 2017), thus accounting for the vast majority of NMSCs. The results are consistent with the literature data carried out both at national and international level. Conclusions: Proper monitoring of this phenomenon through timely reporting and recording of all new NMSC cases is necessary to develop new preventive strategies.